ChemInform Abstract: (H3O)2NaAl3F12, Isostructural with A2NaAl3F12 (A: K+, Rb+, Cs+) Fluorides Having HTB‐Type Sheets. Issue 28 (15th July 2014) - Jouffret, Laurent; Lhoste, Jerome; Hemon‐Ribaud, Annie; Leblanc, Marc; Maisonneuve, Vincent
Abstract (H3O)2NaAl3F12 is obtained as minor phase from the solvothermal reaction of Al(OH)3, NaOH, 1, 2, 4‐triazole, and 40% aq.